EFEKTIVITAS LAYANAN KONSELING KELOMPOK MEDIA YOUTUBE VIDEO DENGAN TEKNIK MINDFULNESS THERAPY UNTUK MENGURANGI OVERTHINKING SISWA KELAS X SMA TUNAS KELAPA SAMARINDA - Ainun Nisa; Rury Muslifar; Dwi Sona; Muhaimin Abdillah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study addresses the rising prevalence of overthinking among adolescents, which has been linked to decreased academic performance, emotional disturbances, and unhealthy social relationships. A quantitative approach was used with a true experimental design involving pre-test and post-test control groups. The participants consisted of six students selected through purposive sampling and divided into two groups: the experimental group received group counseling incorporating mindfulness therapy, while the control group received no intervention. The results revealed a significant reduction in overthinking levels in the experimental group, with the average pre-test score decreasing from 93 to 57.6 in the post-test. In contrast, the control group showed an insignificant change, from 92.3 to 90.6. The t-test analysis showed a significance value (2-tailed) of 0.001 < 0.05, indicating a statistically significant difference between the two groups. Furthermore, the N-Gain Score for the experimental group was 37.99%, categorized as moderate, whereas the control group scored only 1.78%, categorized as low or ineffective. These findings suggest that group counseling with mindfulness therapy is moderately effective in reducing overthinking in students